Body force modelling for axial and centrifugal compressor pre and post-stall aerodynamics - Lamprakis, Dimitrios (Cranfield University, 2022)
The operation of a jet engine is limited in a way to ensure that the manifestation, propagation and growth of local flow compressor instabilities is prevented. This inevitably leads to more conservative compressor designs with increased surge margins and reduced operating range to avoid the occurrence of unstable compressor phenomena. These instabilities are known as rotating stall and surge and their implications on the structural integrity and operability of the engine can be catastrophic. These phenomena and the inception mechanisms that trigger their occurrence are not yet fully understood, while the knowledge gap is exacerbated when considering centrifugal or axi-centrifugal configurations. The cost of experimental campaigns for the investigation of the post-stall response of aero-engine compression systems is excessive, while the compressor is usually restricted to low rotational speeds to prevent severe structural damage. The experiments can only be performed at a more advanced, mature phase of the compressor design process. Sophisticated transient simulations using commercial CFD software offer an alternative approach but the excessive associated computational cost requirements make their real-life usage challenging. Through-flow codes combining reduced and higher-order modelling methods are a computationally efficient alternative, however very few validated implementations are reported in the literature and their capabilities are strictly limited to axial compressor configurations. A lower-order modelling approach is developed, whereby the compression system is solved as an empty duct with body force-fields imparting turning and losses to the flow. A new body force model, applicable to all types of blades is developed. The blade curvature is fully defined in three dimensions accounting for axial, circumferential, radial forces and blade leaning. The flow-field solution is obtained transiently by solving the 2D axisymmetric Euler equations on a body force-relevant grid which ensures that the grid lines are aligned with bladed domains. The governing equations with blockage in the relative frame of reference are derived, thus replicating both metal and aerodynamic blockage effects, along with a method for the precise definition of the additional blockage terms in convoluted ducts. The Godunov scheme coupled with 3 Riemann solvers is used to obtain the fluxes. New analytical, simplified models are derived to estimate aerodynamic blockage and mixing losses at reverse flow conditions in impeller and axial blade passages. Loss correlations are used to estimate losses at forward flow conditions, while mixed and reverse flow are treated with a separate model. The validity and limitations of the different modelling approaches are investigated extensively using test-case scenarios and CFD data. The validation of the overall through-flow framework is carried out on axial compressor and centrifugal compressor stages using CFD and if available, experimental data. Steady-state, forward and reverse flow characteristics are in good agreement with CFD and experimental data, while the flow-field is reproduced with reasonable accuracy. Transient, post-stall simulations in centrifugal compressors are carried out and validated against experimental data. The code constitutes the first successful, validated, through-flow approach, capable of predicting the post-stall, steady-state and transient aerodynamic performance in centrifugal compressors.
Tunstall, Richard - Industrial Supervisor Mazur, Steven - Industrial Supervisor Harvell, John - Industrial Supervisor
Keywords: blade curvature; axial force; radial force; blade leaning; circumferential force; blockage effects